+0  
 
0
22
1
avatar

Solve for x: (3x + 12)(x + 4) = (4x^2 + 8x + 8x^2)/(2x).

 Nov 13, 2022
 #1
avatar+17 
0

I'm assuming you're solving \((3x+12)(x+4) = \frac{4x^2+8x+8x^2}{2x}\). With this, start by simplifying the RHS (right hand side) to \(2x+4+4x\), which is equal to \(6x+4\)

 

 

Now, expand the LHS (left hand side) to get that \(3x^2+24x+48 = 6x+4\). Shift the stuff on the RHS to the LHS to get \(3x^2+18x+42=0\). Using the quadratic equation, the answers are \(x=-3 + \sqrt{5}i\) and \(x = -3-\sqrt{5}i\) (complex roots). 

 

Hope this helped laugh

 Nov 13, 2022

25 Online Users

avatar